An Appraisal of Female Sex Work in Nigeria : Implications for Designing and Scaling Up HIV Prevention Programmes - Ikpeazu, Akudo; Momah-Haruna, Amaka; Madu Mari, Baba; Thompson, Laura H.; Ogungbemi, Kayode (Public Library of Science, 2015)
The HIV epidemic in Nigeria is complex with diverse factors driving the epidemic. Accordingly, Nigeria's National Agency for the Control of AIDS is coordinating a large-scale initiative to conduct HIV epidemic appraisals across all states. These appraisals will help to better characterize the drivers of the epidemic and ensure that the HIV prevention programs match the local epidemic context, with resources allocated to interventions that have the greatest impact locally. Currently, the mapping and size estimation of Female Sex Workers (FSWs) - a major component of the appraisal has been completed in seven states. These states are using the data generated to plan, prioritize and scale-up sub-national HIV prevention programs.